Sensitive and Label‐Free Electrochemical Immunosensor for Alpha Fetoprotein Based on N‐Doped Hollow Nanocarbon Spheres Decorated with Gold Nanoparticles. Issue 13 (3rd April 2023) - Lu, Shiyun; Lin, Yun; Lin, Zhihui; Shi, Bing
Abstract: Alpha fetoprotein (AFP) is an important biomarker in the diagnosis of liver cancer, thus designing simple and effective method to detect AFP great significance. In this work, N‐doped hollow nanocarbon spheres decorated with gold nanoparticles (NHNS/Au) hybrids were produced and adopted as the material for modifying electrode to assemble a simple and sensitive label‐free electrochemical immunosensor of AFP. Scanning‐/transmission‐electron microscopy, energy‐dispersive X‐ray technology and electrochemical methods were introduced to characterize the NHNS/Au nanohybrids; and AFP antibody was assembled on the modified electrode surface based on "Au−S" bond between Au and antibody. By introducing [Fe(CN)6 ] 4−/3− as the signal probe, its electrochemical signal can be suppressed when AFP was bonded by AFP antibody, thus a simple and effective immunosensor of AFP was constructed. After optimizing the related testing conditions, a wide linearity from 0.0 to 15.0 ng mL −1 and a low analytic limitation of 0.06 pg mL −1 were achieved for AFP analysis. Furthermore, the proposed simple and label‐free immunosensor was applied successfully in human serum for AFP analysis and the received results are satisfactory, revealing the designed proposal offers a significant clinical application for AFP detection. Abstract : A sensitive and label‐free electrochemical immunosensor of alpha fetoprotein was designed based on N‐doped hollow nanocarbon spheres decorated with gold nanoparticles, a wide linearity coupled with a low detection limit were achieved successfully.